2009
DOI: 10.1126/science.1164551
|View full text |Cite
|
Sign up to set email alerts
|

Function of Mitochondrial Stat3 in Cellular Respiration

Abstract: Cytokines such as interleukin-6 induce tyrosine and serine phosphorylation of Stat3 that results in activation of Stat3-responsive genes. We provide evidence that Stat3 is present in the mitochondria of cultured cells and primary tissues, including the liver and heart. In Stat3−/− cells, the activities of complexes I and II of the electron transport chain (ETC) were significantly decreased. We identified Stat3 mutants that selectively restored the protein's function as a transcription factor or its functions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

61
1,024
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 900 publications
(1,112 citation statements)
references
References 15 publications
61
1,024
4
2
Order By: Relevance
“…Mitochondria from the hearts of stat3 flox/flox/cre (stat3 ¡/¡ ) and Stat3 flox/flox (wild-type) mice were assayed for complex I and II activities. 37 ETC assays confirmed that stat3 ¡/¡ heart mitochondria have defects in complexes I and II but have normal complex III activity. Using transgenic mice generated with cardiomyocyte-restricted expression of STAT3 that was targeted to the mitochondria with a MLS and containing mutations in the DNA-binding domain (MLS-STAT3E), Szczepanek et al 69 discovered that ischemia increases the release of H 2 O 2 in WT mitochondria respiring on glutamate and malate, whereas no such effect is observed in mitochondria expressing MLS-STAT3E.…”
Section: Regulation Of Autophagy By Mitochondrial Stat3mentioning
confidence: 77%
See 3 more Smart Citations
“…Mitochondria from the hearts of stat3 flox/flox/cre (stat3 ¡/¡ ) and Stat3 flox/flox (wild-type) mice were assayed for complex I and II activities. 37 ETC assays confirmed that stat3 ¡/¡ heart mitochondria have defects in complexes I and II but have normal complex III activity. Using transgenic mice generated with cardiomyocyte-restricted expression of STAT3 that was targeted to the mitochondria with a MLS and containing mutations in the DNA-binding domain (MLS-STAT3E), Szczepanek et al 69 discovered that ischemia increases the release of H 2 O 2 in WT mitochondria respiring on glutamate and malate, whereas no such effect is observed in mitochondria expressing MLS-STAT3E.…”
Section: Regulation Of Autophagy By Mitochondrial Stat3mentioning
confidence: 77%
“…Normally, the pool of mitoSTAT3 is approximately one-tenth of the amount of STAT3 in the cytosol, yet increasing accumulation of mitoSTAT3 appears in response to various stimuli such as ischemia. 37,38 The translocation of STAT3 into the mitochondria was reported to be regulated by NDUFA13, a component of the electron transport chain (ETC) complex I. Interestingly, NDUFA13 was found to colocalize and interact with Ser727-phosphorylated STAT3 in the mitochondria. As Wegrzyn and colleagues 37 found, the immunoprecipitates of mitochondrial extracts yielded from mouse liver captured by a monoclonal antibody specifically targeted to the components of the ETC complex I contained STAT3 and NDUFA13.…”
Section: The Structure and Subcellular Localization Of Stat3mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, STAT3 is required for cell transformation downstream of several oncogenes, the prototype being v-Src (3), which triggers STAT3 Y-P. Recently, S-P induced by activated RAS was shown to trigger tumour transformation, driving STAT3 to localize to mitochondria and regulate cellular respiration (4,5). This non canonical activity is required for RAS-dependent oncogenic transformation.…”
mentioning
confidence: 99%